Archaeological finds from Križna jama cave - Bavdek, Alma; Mihevc, Andrej; Toškan, Borut; Velušček, Anton (Arheološki vestnik, 2009)
This paper discusses the archaeological finds from the speleologically important Križna jama cave, located in the Notranjska region. Since 1955, the cave has been open for tourist visits.From the end of the 19th century, the cave had been known in scientific circles mostly because of the pale-ontological remains of cave bear (Ursus spelaeus). It was only as late as 1973 when the cave was recognised as an archaeological site; however, it has remained unknown to the wider professional public until the present.No anthropogenic structures have been discovered in the cave. One exception is perhaps plateau 1, at the entrance of the cave, where researchers came across some charcoal flecks and pottery fragments.The earliest archaeological finds can be dated to the C opper Age. However, chronologically reliable finds originate broadly from the Middle Bronze Age, which is also the period of the earliest human visits to the cave. Individual finds and inscriptions on the walls of the cave indicate that people have been, for one reason or another, visiting the cave ever since.